An isolated hand tumour as primary manifestation of sarcoidosis - Altmann, S.; Schreiber, J.; Damert, et al., H-G. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2011)
Background: Sarcoidosis is a systemic disorder with unknown etiology, characterized by non-caseating granulomas in numerous organs and tissues. In 90% of patients lung and lymph nodes are involved.The incidence of sarcoidal granulomas in the upper extremities is low. Here we present the case of a primary hand manifestation of sarcoidosis without clinical systemic involvement. Objectives: A young woman presented with a painful swelling in her right hand.There were no signs of inflammation. Normal perfusion, mobility and sensibility were found. Magnetic resonance imaging (MRI) revealed a tumour infiltrating the muscles and flexor tendons of the third digit around the metacarpal bone and with pathological signal enhancement after administration of contrast medium. Results: Intraoperatively, nodular masses and fat tissue were seen.Histological examination after radical tumour resection showed sarcoidal granulomas. Postoperative staging diagnostics with computed tomography (CT) demonstrated multiple thoracic lymph node swellings in the mediastinum and bilateral hili. Follow-up after one year we saw normal scars in the palmar hand. There was no sign of local recurrence. The pulmological care is still going on. Conclusions: Sarcoidosis is a rare, often asymptomatic disease. Patients present with dyspnoe and cough caused by the inflammation of the lung. The first clinical manifestation of sarcoidosis as a tumor in the palmar hand is unusual. Extrapulmonary systemic or progressive sarcoidosis is regarded as an indication for therapy with glucocorticosteroids. This case demonstrates that surgical excision enabled complete local cure without necessity of systemic and/or local treatment with steroids.